Power quality assurance in the electrical network of the Syrian Arab Republic, using the active power filter - R. R. Nasyrov; R. Aljendy; T. Kherbek (Известия высших учебных заведений: Проблемы энергетики)
The set of characteristics that determine the power quality (PQ) can be used to describe the state and efficiency of the power supply system in terms of the influence of electromagnetic interference. The impact of electromagnetic interference on electrical equipment is manifested in the reduction of uptime, additional losses of active power, data loss, etc. The most common sources of interference in modern conditions are consumers with non-linear volt-ampere characteristics. This type of electrical receivers creates a distortion of the current and voltage waveform. In view of the widespread use of these power consumers in daily life and industry, special attention should be paid to the problems of harmonic distortion. This article presents the results of measurements and analysis of the quality of electricity, and also shows the effect of applying an active filter (AF) to ensure the quality of electricity in the distribution network (66/20 kV) of the city of Lattakia in the Syrian Arab Republic. The definition of the optimal capacitance of the AF dc link using the particle swarm method is given in order to minimize the total non- sinusoidal current and voltage in the studied electrical network.